Hand Grasping Synergies As Biometrics - Patel, Vrajeshri; Thukral, Poojita; Burns, Martin K.; Florescu, Ionut; Chandramouli, Rajarathnam; Vinjamuri, Ramana (Frontiers in Bioengineering and Biotechnology, 2017)
Recently, the need for more secure identity verification systems has driven researchers to explore other sources of biometrics. This includes iris patterns, palm print, hand geometry, facial recognition, and movement patterns (hand motion, gait, and eye movements). Identity verification systems may benefit from the complexity of human movement which integrates multiple levels of control (neural, muscular, and kinematic). Using principal component analysis we extracted spatiotemporal hand synergies (movement synergies) from an object grasping dataset to explore their use as a potential biometric. These movement synergies are in the form of joint angular velocity profiles of ten joints. We explored the effect of joint type, digit, number of objects, and grasp type. In its best configuration, movement synergies achieved an equal error rate (EER) of 8.19%. While movement synergies can be integrated into an identity verification system with motion capture ability, we also explored a camera-ready version of hand synergies—postural synergies. In this proof of concept system, postural synergies performed well, but only when specific postures were chosen. Based on these results, hand synergies show promise as a potential biometric that can be combined with other hand based biometrics for improved security.